Hepatoprotective Effects of Ageratum conyzoides L. on Biochemical Indices Induced by Acetaminophen Toxicity in Wistar rats - Pawan K Verma, M Sultana, R Raina, S Prawez, S Pandita, Neha Jamwal and Arshad H Mir (Journal of Applied Pharmaceutical Science, 2013)
Ageratum conyzoides L. (Compositae) has been used in various parts of the world for the treatment of various diseases based on their age-old use in folklore system. Present study was aimed to investigate the hepatoprotective activity of acetone and n-hexane extracts of Ageratum conyzoides in wistar rats following acetaminophen (APAP) induced hepatotoxicity. Single high dose exposure of APAP significantly (p
Keywords: Hepatotoxicity, acetaminophen, biochemical